ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PILIHAN PETANI MELAKUKAN ALIH USAHATANI DI KECAMATAN RIO PAKAVA KABUPATEN DONGGALA - Nurmedika Nurmedika; Muhammad Basir-cyio; Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
The purpose of this study was to determine the factors that affect farmers' choice to switch the cocoa farming to palm farming in the district of Rio Pakava Donggala Regncy. The study was conducted in the District of Rio Pakava Donggala Regency in November 2014 to January 2015. The study used quantitative and qualitative approach with a sample size of 50 respondents, comprised of 25 cocoa farmers and 25 oil palm farmers who switch cocoa farming into farming oil palm. The study, carried out using non-probability sampling method is caused by the amount of each population to be studied is not known exactly, using purposive sampling, the expected criteria for samples obtained completely according to the research conducted, to obtain a representative sample, making the subject of each region is determined by or in proportion to the number of subjects each region.  Based on the analysis using logit models indicate that the variable cost of production of cocoa and income influence the decision of farmers switch of cocoa farming to oil palm farming, while the variable land and labor flow has no effect on the decision of farmers to switch cocoa farming into palm oil farming Key words : Option farmer, switch cocoa farming to palm oil farming.